Pariwisata Olahraga (Sport Tourism) Meningkatkan Pertumbuhan Ekonomi Masyarakat Di Kabupaten Kerinci - Mardiana Ningsih; Rio Prasetya; Sindy Ningsih (Jurnal Sporta Saintika, 2025)
Sport Tourism is one of the contributions of tourism sports that can have a great influence on the community's economy. The purpose of this study is to identify the potential of sports tourism in Kerinci Regency. This study uses a qualitative descriptive approach using observational research tools and semi-structured questions and answers. The results of the research conducted show that the sport tourism event is very effective in increasing tourism and economic visits in Kerinci Regency. This research contributes to the development of sports tourism potential in Kerinci Regency. Conclusion: Sports tourism increases the economic growth of the community in Kerinci Regency. Therefore, sports tourism must always be developed so that Kerinci Regency can be better known outside the province and even become famous in foreign countries. For the next researcher, it is recommended to see how the public's perception of an event is held, and also how other researchers can see the impact of an event on other sectors.